KONTRIBUSI KREATIVITAS BELAJAR DAN PEMANFAATAN LABORATORIUM KOMPUTER TERHADAP HASIL BELAJAR PEMOGRAMAN WEB DI SMK N 1 JULOK - Syafariah Syafariah; Hanesman Hanesman (Universitas Negeri Padang, 2019)
SMK Negeri 1 Julok is a school that teaches several skills programs to promote Software Engineering (RPL) expertise programs, in this case students are still not optimal on learning outcomes on KKM which have been identified in the Web Programming course on the 2018/2019 semester exam, students those who get results that have achieved KKM are less than students who have not achieved mastery, students who get more scores from KKM 60% KKM are determined in pairs of web programming lessons which are 75 with values ranging from 0-100, therefore the type of research that take the type of correlational descriptive research. The population taken in this study which took 30 students in class X Software Engineering Engineering (RPL) in the thesis research that the authors compiled resulted in the sample technique used in total sampling. Results show between 1). Learning effectiveness and benefits of a fully shared laboratory contributed 49.5% ‘2). Creativity contribution Students' interest in learning is 38.5%, towards learning outcomes. 3). LAB Computer provides a contribution of 38.6%, special learning outcomes for WEB subjects in the upper classes of RPL software engineering techniques in SMK Negeri 1 Julok. What I can conclude is that the higher the learning creativity, the greater the use of computer LAB, the greater the agreed upon results obtained from learning. Keywords: Computer Laboratory, Creativity, Learning Outcomes.